STRATEGI PEMASARAN PRODUK PEMBIAYAAN DALAM MENINGKATKAN JUMLAH NASABAH PADA BMT AL HIDAYAH UMMAT SEJAHTERA - marjan; Iswandi, L. Muhamad (MUSLIMPRENEUR : Jurnal Ekonomi dan Kajian Keislaman, 2024)
This research aims to determine the Marketing Strategy for Financing Products in Increasing the Number of Customers at BMT Al Hidayah Ummat Sejahtera Kotaraja. This research uses field research with a qualitative approach, namely direct observation of the object under study in order to obtain relevant data. Based on the results of the research that the author obtained regarding Marketing Strategy for Financing Products in Increasing the Number of Customers at BMT Al Hidayah Ummat Sejahtera Kotaraja, namely by implementing product strategy, price strategy, place/distribution strategy (place), promotion strategy and HR strategy in marketing activities. The obstacles faced in the Marketing Strategy for Financing Products in Increasing the Number of Customers at BMT Al Hidayah Ummat Sejahtera Kotaraja include: External obstacles; 1) Very tight competition with other financial institutions, 2) Lack of public knowledge or understanding about BMT, 3) There are many other financial institutions standing. Constraints from within; 1) Administration sector, 2) HR sector.